2013
DOI: 10.1097/phm.0b013e31826edc7b
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Extracorporeal Shock Wave Therapy vs. Local Steroid Injection for Management of Carpal Tunnel Syndrome

Abstract: ESWT can be as useful as CS injection for relieving symptoms of carpal tunnel syndrome. Furthermore, in contrast to CS injection, it has the merit of being noninvasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 6 publications
3
74
2
1
Order By: Relevance
“…A few studies have tried to apply ESWT as an alternative management for treating peripheral neuropathy, for example interdigital neuroma28, stump neuroma29, distal symmetric polyneuropathy30, and CTS131415, with inspiring results. In 2013, Seok et al 13. first reported that one-session fESWT could be as useful as corticosteroid injection for relieving symptoms of CTS (n = 15 vs. n = 16 respectively), and that the effect could persist for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have tried to apply ESWT as an alternative management for treating peripheral neuropathy, for example interdigital neuroma28, stump neuroma29, distal symmetric polyneuropathy30, and CTS131415, with inspiring results. In 2013, Seok et al 13. first reported that one-session fESWT could be as useful as corticosteroid injection for relieving symptoms of CTS (n = 15 vs. n = 16 respectively), and that the effect could persist for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why we did not observe a noteworthy benefit after single-session rESWT compared with sham rESWT, although much greater improvements in BCTQ, most SNCV and CSA were observed. Most previous studies applied 3 sessions of ESWT in treating CTS except the study by Seok et al 13,. which used single-session fESWT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two case reports on patients treated with SW for CTS, the authors found a clinical and electromyographic improvement. 5 A clinical trial on 36 patients affected with CTS 6 verified that ESWT can be as useful as a CS injection for relieving symptoms of CTS. Furthermore, in contrast to the CS injection, it has the merit of being non-invasive.…”
Section: Introductionmentioning
confidence: 99%